2020
DOI: 10.29309/tpmj/2020.27.04.3683
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of erythropoietin in correcting anemia in patients of chronic kidney disease.

Abstract: Objectives: The anemia of chronic kidney disease (CKD) is commonly normocytic and normochromic. The objective of current study was to see the effectiveness of erythropoietin in correcting anemia in children with CKD. Study Design: Descriptive case series. Setting: Department of Nephrology, at The Children’s hospital and the institute of child health, Multan. Period: From March 2018 to September 2018. Material & Methods: A total of 79 children with CKD were enrolled in this study. A standard dose of erythro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…A study conducted by Shuaib et al 17 has also reported 24.97±15.88 kilograms mean weight of the children undergoing hemodialysis. Shakir et al 18 has also reported 19.65± 4.71 kilograms mean weight, similar to our results. Jaramillo et al 19 from Mexico has also reported similar results.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A study conducted by Shuaib et al 17 has also reported 24.97±15.88 kilograms mean weight of the children undergoing hemodialysis. Shakir et al 18 has also reported 19.65± 4.71 kilograms mean weight, similar to our results. Jaramillo et al 19 from Mexico has also reported similar results.…”
Section: Discussionsupporting
confidence: 93%
“…A study conducted by Shuaib et al 17 has also reported 11.91±7.06 months mean duration on hemodialysis, close to our study results. Shakir et al 18 has also reported similar results. Jaramillo et al 19 from Mexico has also reported similar results.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation